Comparative Study on Modified Thiel and Saturated Salt Embalming Technique of Cats (Felis catus) Cadavers for Teaching Veterinary Anatomy - Harish Gavand; S. Gaikwad; S. Ingole; V. Shankhpal; D. Kadam; S. Lambate; P. Mahanwar (Indian Journal of Veterinary Anatomy, 2024)
Embalming of cadavers has been an important part of the veterinary anatomy curriculum. Modern embalming solutions like Thiel embalming solution and Saturated salt embalming solution were used. Six cadavers of respective embalming solutions were evaluated for parameters like colour retention, skin conditions, cost analysis, odour post one month of embalming. Results of colour retention, skin conditions, odour, and eye irritation parameters were evaluated using questionnaires answered by veterinary undergraduates. Comparative costing resulted that the Thiel embalming solution was costlier than the Saturated salt embalming solution. On the evaluation of life-like conditions, colour retention by students it was observed that Thiel-embalmed cadavers were slightly superior to Saturated salt-embalmed cadavers. No eye irritation or skin irritation while handling and dissecting both types of cadavers. The skin conditions of both cadavers were fine. A slight cadaverine odour was observed by the students while handling Thiel embalmed cadavers. In conclusion, both types of embalming solutions can act as a good substitute to the traditional embalming solution. A comparative study indicates saturated salt embalming solution to be a better embalming solution in academics due to its low cost and long durability.